Factores condicionantes de las mipymes y su impacto en el desarrollo de la economía familiar del Cantón Quevedo año 2023 - Mosquera Quintana, Zaida Gissel (2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the global economy due to their significant contribution to economic growth, job creation and innovation. In order to obtain the results for this research, the main objective was to evaluate the impact of the conditioning factors of MSMEs on the development of the family economy of the Quevedo canton. To achieve this purpose, a series of strategies were carried out focused on four main areas: access to financing, business training, improvement of infrastructure and promotion of favorable policies for MSMEs. For this, an interview was carried out with the president of the commercial chamber of the Quevedo canton and a survey of the different families regarding the topic. Through collaboration with financial institutions, government agencies, civil society organizations and local actors, we sought to create an environment conducive to the growth and sustainability of MSMEs. It was expected that this project would contribute significantly to the strengthening of the business sector, the generation of employment and the revitalization of the local economy in the Quevedo Canton. MSMEs play a fundamental role in the economic and social fabric, and their support and development are essential for the sustainable growth and prosperity of communities and countries around the world.